POOR AND PLANTATION COMMODITIES DISTRIBUTION INFORMATION SYSTEM TO POVERTY REDUCTION IN WEST JAVA PROVINCE - Afrianto, Irawan (Badan Penelitian dan Pengembangan Daerah (BP2D) Provinsi Jawa Barat, 2017)
The number of poverty in West Java Province reaching 4.23 million / 9.18%, is a matter of special concern for the government of West Java Province to perform the actions and activities of poverty reduction. Meanwhile, West Java with 26 districts / cities has a huge plantation potential, there are 493,118 hectares of plantations in West Java with 33 plantation Commodities therein. This led to a desire to collaborate on poverty data and potential plantation data in order to reduce the poverty rate. Geographic information system (GIS) which contains data and distribution of poor communities and plantations developed to map the areas that have poor communities and the potential of plantations in the area. This is intended to facilitate the provision of assistance from the Plantation Office for poor communities around the plantation. The system development method used is UCD (User Centered Design) so that it can focus on the needs of data and information needed. The use of maps with the google maps API provides ease in presenting regional spatial data to show poverty data as well as plantation potential. The existence of mapping system of distribution of poor people and plantation potency hence information of location of poor society and potency of plantation in West Java can be raised in one information intact to facilitate in informing of poor society that domicile around plantation.